ANALISIS EFISIENSI PERUSAHAAN PERTANIAN DI INDONESIA DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - Utari, Tarisa Rama; Rahmah, Mutia; Murtala, Murtala; Juanda, Reza (LPPM Universitas Malikussaleh - Indonesia, 2023)
This study aims to determine the condition of the company, efficient or not through the efficiency analysis test. The method in this analysis test is non-parametric quantitative with Data Envelopment Analysis (DEA) model. The data source is based on the financial statements of agricultural companies, where the input variables include; Total Assets, Liabilities and Land, while the output variable is Sales. Processed using MaxDea software. There are 12 sample companies or DMU in this study. The results of DMU analysis using VRS output orientation assumptions show that agricultural companies that are on an efficiency scale of 1 are 4 companies.